2001
DOI: 10.1097/00004728-200105000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Encasement by Pancreatic Cancer: Correlation of CT Findings with Surgical and Pathologic Results

Abstract: The grading system of vascular invasion should differ between arteries and veins. Involvement of the venous system exceeding one-half circumference of the vessels (grade 3 or 4) was suggestive of vascular invasion; however, this criterion was not always satisfactory for the evaluation of tumor invasion in the arterial system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 24 publications
2
21
0
2
Order By: Relevance
“…Brügel et al (33) reported that the probability of vascular invasion in cases that had Lu grade 2 criteria on axial images was 50%. As a result of their studies, in which Lu criteria were used, Nakayama et al (34) suggested that different criteria should be used to evaluate vascular involvement. Researchers noticed that Lu criteria are not be useful in determining vascular invasion if there is inflammatory or fibrous tissue around the peripancreatic arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Brügel et al (33) reported that the probability of vascular invasion in cases that had Lu grade 2 criteria on axial images was 50%. As a result of their studies, in which Lu criteria were used, Nakayama et al (34) suggested that different criteria should be used to evaluate vascular involvement. Researchers noticed that Lu criteria are not be useful in determining vascular invasion if there is inflammatory or fibrous tissue around the peripancreatic arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the distinction between vascular invasion and inflammatory adhesions is not always obvious on preoperative imaging or intraoperatively. Nakayama et al [35] showed that preoperative CT scan has a low accuracy (79%) for detection of arterial invasion. In fact, in spite of the apparent preoperative tumoral encasement of large peripancreatic arteries (celiac trunk, SMA, hepatic artery) the arterial wall invasion was rarely confirmed by the histopathology (10%) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Using a scale from 0 to 4 for circumferential contiguity of tumor to vessel in order to evaluate vascular involvement, Nakayama et al [28] found that a grading system of vascular invasion should differentiate between arteries and veins. Li et al [24,25] used different diagnostic criteria for evaluating venous and arterial invasion with the argument that, as the venous wall is thinner and weaker than the muscular arterial wall, the vascular changes indicating invasion will be different.…”
Section: Discussionmentioning
confidence: 99%